2011
DOI: 10.1021/pr200395b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multiprotein Complexes of the Borrelia burgdorferi Outer Membrane Vesicles

Abstract: Amongst bacterial cell envelopes, the Borrelia burgdorferi outer membrane (OM) is structurally unique in that the identities of many protein complexes remain unknown; however, their characterization is the first step towards our understanding of membrane protein interactions and potential functions. Here, we used two-dimensional blue native/SDS-PAGE/mass spectrometric analysis for a global characterization of protein-protein interactions as well as to identify protein complexes in OM vesicles isolated from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 81 publications
6
66
0
Order By: Relevance
“…5A and C). Previous studies have shown that OspA and P66 can be coimmunoprecipitated after cross-linking of B. burgdorferi cells (71,72). Consistent with these results, OspA was detected in a high-molecular-mass complex that migrated similarly to the large ϳ600-kDa P66-band II complex (Fig.…”
Section: P66 Is Part Of a Higher-order Complex And Associates Withsupporting
confidence: 87%
See 2 more Smart Citations
“…5A and C). Previous studies have shown that OspA and P66 can be coimmunoprecipitated after cross-linking of B. burgdorferi cells (71,72). Consistent with these results, OspA was detected in a high-molecular-mass complex that migrated similarly to the large ϳ600-kDa P66-band II complex (Fig.…”
Section: P66 Is Part Of a Higher-order Complex And Associates Withsupporting
confidence: 87%
“…Previous experiments have revealed an interaction between P66 and borrelial surface lipoproteins (71)(72)(73). According to the results of the BN-PAGE experiments reported here, recombinant P66 migrates at a much lower molecular mass than native P66, indicating that P66 is a member of a large protein complex in the borrelial OM.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Because of its RGD integrinbinding motif and the ability of BB0744 to bind to ␤ 1 integrins (21), specifically ␣ 1 ␤ 1 (not shown), we hypothesized that BB0744 may use a leader peptidase I signal sequence to be exported to the cell envelope and be surface exposed within the outer membrane of B. burgdorferi. The localization of this protein in outer membrane vesicles provided further evidence that BB0744 might be surface exposed (43). However, multiple approaches suggested that, while exported, BB0744 was not surface exposed, despite its association with outer membrane vesicle preparations during integrin binding screening (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The impact and role of BB0744 during infection have not been previously studied, but it is a known serodiagnostic antigen for Lyme infection (40)(41)(42). BB0744 has also been observed forming complexes with other proteins isolated in outer membrane vesicles, suggesting an association with the outer membrane envelope (43). In this study, we show that BB0744 is required for optimal tissue tropism and/or normal dissemination in mice infected by needle inoculation given that B. burgdorferi strains lacking this gene exhibit a defect in colonization to both distal skin sites and the heart and exhibit reduced bacterial loads in lymph node and joint tissues.…”
mentioning
confidence: 99%